BS22 Double positive (CD86+ MRC1+) inflammatory macrophages in the pathogenesis of carotid atherosclerosis. (May 2019) - Kocsy, Klaudia; Francis, Sheila; Kiss-Toth, Endre; Lonsdale, Robert; Majid, Arshad; Redgrave, Jessica
Abstract : Introduction: Atherosclerosis is a complex inflammatory disease in which major arteries narrow, and an atherosclerotic plaque develops, modulated by genetic and environmental factors. Macrophages participate in all stages of the plaque formation and progression. Different macrophage subtypes within carotid plaques have been shown to be altered in unstable vs. stable plaques. M1 proinflammatory macrophages are mostly abundant in symptomatic and unstable plaques. In contrast, M2 macrophages are associated with regulatory and wound-healing properties and generally found in stable lesions. In the future, the characterisation of these changes in situ in the carotid plaques, associated with in vitro macrophage studies, and blood composition may lead to the identification of diagnostic markers to direct the best treatment for stroke patients. Methods: Carotid plaques were obtained from patients with a recent stroke or TIA and with a greater than 50% stenosis of the internal carotid artery. Plaques were removed during carotid endarterectomy and fixed in 10% (v/v) neutral buffered formalin for maximum 36h. Macrophage phenotypes within the shoulder regions were characterised with immunofluorescence microscopy. A novel immunofluorescence staining, image acquisition and analysis technique was developed to identify single M1 (CD68+CD86+MRC1-), single M2 (CD68+CD86-MRC1+), double positive (CD68+CD86+MRC1+) and double negative (CD68+CD86-MRC1-) macrophages in the human carotid atherosclerotic plaques. Results: 20 carotid plaques were collected from patients with recent stroke or TIA (73% male, 70% smokers, 87% hypertensive). In 17 plaques the shoulder region (either side of a thinned fibrous cap) was sufficiently intact for histological analysis. Dense infiltration with macrophages was seen in all 17 specimens. The population comprised double positive (CD86+MRC1+) (71%), M1 single positive (CD86+MRC1-) (19%), and M2 single positive (CD86-MRC1+) (4%). Double negative (CD86-MRC1-) macrophages represented 6% of all macrophages. Amongst 10 unstable plaques (defined as AHA Grade 6 or above) the majority (80%) of shoulder macrophages were M1 single positive. In contrast, amongst 7 stable plaques, the majority of plaque shoulder macrophages (65%) were M2 single positive. Conclusions: Macrophages within symptomatic carotid plaques can express both M1 (CD86) and M2 (MRC1) markers, or can express neither. Pro-inflammatory macrophage phenotypes cluster in areas of unstable carotid plaque. Larger studies are needed to confirm the role of dual staining macrophages and double negative macrophages. If such in situ macrophages can be manipulated towards one phenotype with pharmaceutical interventions, this could offer a potential new approach to plaque stabilising therapies. Conflict of interest: No